1999
DOI: 10.1023/a:1006947015094
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Small proteoglycans (PGs) are supposed to play great roles in the assembly of cartilage matrix but the influence of cytokines and growth factors on their synthesis by articular chondrocytes is largely unknown. We investigated whether IL-1 and TGFbeta1 influence the production of small leucine-rich proteoglycans by chondrocytes cultured in a three-dimensional gel, as compared to the common monolayer system. Rabbit articular chondrocytes were cultured in alginate beads for 14 days or as monolayers for 7 days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…A potential limitation of the current study is that the use of 2D culture may alter the NP cell phenotype [44], and may differentially regulate the inflammatory response [45]. However, NPs are known to respond to cytokines both in vivo and in vitro [20], and our findings on biophysical responses are assessed on cells in 3D-like rounded morphology.…”
Section: Discussionmentioning
confidence: 96%
“…A potential limitation of the current study is that the use of 2D culture may alter the NP cell phenotype [44], and may differentially regulate the inflammatory response [45]. However, NPs are known to respond to cytokines both in vivo and in vitro [20], and our findings on biophysical responses are assessed on cells in 3D-like rounded morphology.…”
Section: Discussionmentioning
confidence: 96%
“…These observations have led to evaluations of cartilage destruction using IL-1β or TGF-β. Concerning culturing conditions, Demoor-Fossard et al (30) treated chondrocytes in culture with these cytokines, noted differences in ECM formation between monolayer and three-dimensional cultures, and reported that responses to biological stimuli such as cytokines similar to those of cartilage tissue were observed in three-dimensional cultures. This suggests that the responses observed in the ECM in monolayer cultures may not necessarily reflect physiologic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Potential limitations of the study include the use of cell plating for expansion, which may alter NP cell phenotype ( Horner et al , 2002 ) as well as inflammatory response ( Demoor-Fossard et al , 1999 ). However, for osmotic and cytoskeletal analysis, NP cells were observed in a rounded morphology that more closely mimicked the 3D morphology of NP cells in situ .…”
Section: Discussionmentioning
confidence: 99%